Climate Security Nexus in Latin America and the Caribbean: Venezuela and Colombia - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Castellanos, Andrea; Martínez Barón, Deissy; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The climate crisis is having a significant detrimental influence on livelihoods in developing countries. Climate variability and extremes can negatively impact climate-sensitive sectors such as agriculture and livestock which are a considerable source of employment and a key contributor to economic growth in developing countries (Burke, Hsiang, and Miguel 2015; Dell, Jones, and Olken 2014; 2012). The intensification of the climate crisis poses a threat to efforts aimed to eliminate poverty and food security which, in turn, can threaten peace (United Nations 2020). Despite not being the main or the only cause, there is growing evidence of the importance of food insecurity in sparking and sustaining civil and communal conflicts (FAO 2016).